Strategies to accelerate the contribution of School Feeding Programs to nutritional outcomes: Evidence and Opportunities - Alderman, Harold (2018)
This seminar was held in partnership with WFP under the title of "Utilizing evidence-based research to inform policy: The Case of School Feeding Programs"